(untitled) (Indian Journal of Public Health Research & Development, 2025)
INTRODUCTION: Our understanding of the health system and patient factors responsible for the time delay in diagnosis and treatment is limited. Further research is needed to analyze the health system factors responsible for delay in diagnosis of TB and to identify key factors related to delay in initiation of treatment, in particular the pathways involving health care providers and patients contributing to the complexity and long delays. Hence the current study was undertaken to identify the magnitude of the problem and reasons for delays in diagnosis and treatment using a mixed-method approach. MATERIALS & METHODS: A Mixed –method study was conducted between November 2019 to December 2021 in 8 selected Tuberculosis units (TUs) of Urban Visakhapatnam district, Andhra Pradesh. It comprised of a cross sectional study of 102 people with tuberculosis followed by a series of Focus group discussions (FGD), In-depth interviews (IDI) & Key informant interviews (KII) with patients & health care workers associated with T.B service delivery. RESULTS: The study findings suggested that out of a total 102 study population, the median age of study population was 39 years. Majority (59.8%) were males and 40.2% were females. The median patient care seeking delay was found to be 30 days (IQR 60-1) with a mean delay of 43 days. The mean diagnostic delay duration of 1±1.1 days with no treatment delay was observed in present study population. The mean total patient pathway duration was 44.3±50.2 days. Lack of awareness, fear and stigma derived qualitatively further explained the quantitative findings. CONCLUSION: There were minimal delays observed in the study population in terms of diagnosis and treatment initiation, but a significant proportion of delays were seen in seeking medical care in patient’s pathway to healthcare system. Increasing public awareness about TB and consciousness regarding stigma, engaging the private health care providers could further improve early detection of TB and narrow the gap of missing cases.